Shépa The Tibetan Oral Tradition in Choné - Tso, Bendi (World Oral Literature Series, 2023)
Shépa: 'explanation' or 'elucidation' in Tibetan. A form of oral poetry sung antiphonally in a question-and-answer style. This book contains a unique collection of Tibetan oral narrations and songs known as Shépa, as these have been performed, recorded and shared between generations of Choné Tibetans from Amdo living in the eastern Tibetan Plateau. Presented in trilingual format - in Tibetan, Chinese and English - the book reflects a sustained collaboration with and between members of the local community, including narrators, monks, and scholars, calling attention to the diversity inherent in all oral traditions, and the mutability of Shépa in particular. From creation myths to Bon and Buddhist cosmologies and even wedding songs, Shépa engages with and draws on elements of religious traditions, historical legacies and deep-seated cultural memories within Choné and Tibet, revealing the multi-layered conceptualization of the Tibetan physical world and the resilience of Tibetan communities within it. This vital and unique collection, part of the World Oral Literature Series, situates Shépa in its ethnographic context, offering insights into the preservation and revitalization of intangible cultural heritage in the context of cultural Tibet, Indigenous studies and beyond. Scholars and students in the fields of anthropology, linguistics, ethnic and minority relations, critical Indigenous studies, Tibetan studies, Himalayan studies, Asian studies and the broader study of China will find much to reward them in this book, as will all readers interested in the documentation and preservation of endangered oral traditions, intangible cultural heritage, performance and textuality, and Tibetan literature and religions.